Pathogenesis Based Diagnosis and Treatment of Endometriosis - Koninckx, Philippe R.; Fernandes, Rodrigo; Ussia, Anastasia; Schindler, Larissa; Wattiez, Arnaud; Al-Suwaidi, Shaima; Amro, Bedayah; Al-Maamari, Basma; Hakim, Zeinab; Tahlak, Muna (Frontiers in Endocrinology, 2021)
Understanding the pathophysiology of endometriosis is changing our diagnosis and treatment. Each endometriosis lesion originates from a different clone and cells have specific characteristics as aromatase activity and progesterone resistance. Since being different from the endometrium, the implantation theory has to be replaced. The genetic-epigenetic theory postulates that endometriosis starts with cellular incidents. The subsequent growth in the specific environment of the peritoneal cavity is associated with angiogenesis and an inflammatory immunologic reaction. This and bleeding in the lesions causes fibrosis, which will ultimately stop the growth and result in burnt out lesions. The pain associated with endometriosis lesions is variable, some lesions not being painful, others causing neuroinflammation up to 28 mm distance. Diagnosis of endometriosis is made by laparoscopy, performed after an experience guided clinical decision, based on history, symptoms, clinical exam and imaging. Biochemical markers are not useful. For deep endometriosis, imaging is considered important before surgery, although the available predictive value is rather poor, considering confidence limits, the prevalence of the disease and the absence of stratification of lesions by size, localization and depth of infiltration. Surgery of endometriosis is based on recognition and excision. The surrounding fibrosis belongs to the body with limited infiltration by endometriosis and a rim of fibrosis can be left without safety margins. For deep endometriosis, this results in a conservative excision eventually with discoid excision or short bowel resections. For cystic ovarian endometriosis superficial destruction, if complete, should be sufficient. Understanding pathophysiology changes the discussion of earlier intervention during adolescence. Considering neuroinflammation at distance, the exploration of large somatic nerves should be reconsidered. Medical therapy of endometriosis has to be reconsidered since the variability of lesions results in a variable response, some lesions not requiring estrogens for growth and some being progesterone resistant. If the onset of endometriosis is driven by oxidative stress from retrograde menstruation and the peritoneal microbiome, medical therapy should prevent new lesions and becomes indicated after surgery.